A systematic review on modelling approaches for economic losses studies caused by parasites and their associated diseases in cattle. Issue 2 (2nd August 2018) - Rashid, Muhammad; Rashid, Muhammad Imran; Akbar, Haroon; Ahmad, Liaquat; Hassan, Muhammad Adeel; Ashraf, Kamran; Saeed, Khalid; Gharbi, Mohamed
Abstract: Parasites reside inside or outside their hosts and get host nutrition and blood. Here, we have emphasized economic losses in cattle caused by parasitic diseases due to ecto- and endo- parasites (flies, ticks, mites and helminths). We have outlined different methods/models including economic evaluation techniques and dynamic analysis as a major class, used for the calculation of economic losses caused by parasites in cattle. According to already conducted studies, a decrease in production is mentioned in quantity and percentage while financial losses are expressed in the form of account with respect to per head, herd or for the specific study area. The parasites cause the reduced production and financial losses due to control, treatment and mortality costs. We calculated the average decrease in milk production and organ condemnation as 1.16 L animal −1 day −1 and 12.95%, respectively, from overall cattle parasitic infections. Moreover, the average calculated financial and percentage losses were US 50.67 animal −1 year −1 and 17.94%, respectively. Economically important parasitic diseases mentioned here are caused by specific spp. of protozoans and helminths according to data collected from the literature. Protozoan diseases include tick-borne diseases, coccidiosis, neosporosis, trypanosomiasis and cryptosporidiosis. Losses due to tick-borne infections were encountered for decreased milk production, mortality, treatment and control. Losses from coccidiosis were due to decreased weight gain, treatment costs and mortality. While abortion losses were encountered in neosporosis. Trypanosomiasis caused losses due to a decrease in milk yield. Moreover, only diagnostic (conventional or molecular techniques) cost was taken into account for cryptosporidiosis. Economically important nematode parasites are Oesophagostomum spp., Cooperia spp., Trichostrongylus spp., Strongyloides spp., Ostertagia spp. and Haemonchus placei . Due to the zoonotic importance of echinococcosis, Echinococcus granulosus is the most economically important cestode parasite. Losses caused by echinococcosis were due to organ condemnation, carcass weight loss and decreases hide value, milk production and fecundity. While, fascioliasis is one of the most economically important trematodal disease, which causes cirrhosis of the liver due to parasite migration, and thus, the organ becomes inedible. So, it would be helpful for farmers and researchers to approach these methods/models for calculation of parasitic losses and should adopt suitable measures to avoid long-term economic losses.